Theta‐phase stabilization by rare‐earth and alkali incorporation in sol‐gel derived alumina. (9th July 2021) - Tian, Peijing; Müller, Lenka; Zitnan, Michal; Sajzew, Roman; Wondraczek, Lothar
Abstract: Bottom‐up synthesis of alumina suspensions doped with trivalent (Eu 3+ ) or monovalent (K + ) ions is reported as a means to generate crystalline transition‐phase alumina with increased thermal stability. Dynamic light scattering was used to track the stability of precursor sols, showing how the dissolved cations contribute to the stabilizing double layer and particle separation in the liquid phase. The incorporation of alkali or rare‐earth dopants into the alumina structure further influences the thermal conversion and crystallization behavior. The Kissinger activation energy of the θ → α phase transition in Al2 O3 indicates an inhibitory effect of Eu 3+ and K + on the formation of the stable α phase, also confirmed by X‐ray diffraction. The intensity ratio of the 7 F2 / 7 F1 characteristic photoemission bands of Eu 3+ was used to probe the local symmetry as a function of calcination temperature to further corroborate this observation.